An IPMC actuated robotic surgery end effector with force sensing - Kean Aw; Lixue Fu; Andrew McDaid (International Journal of Smart and Nano Materials, 2013)
Growth in patient acceptance of robotic-assisted surgery has led to increased demand and has stimulated research in many new surgical robotic applications. In some cases, the performance of robotic surgery has proven to surpass that of human surgeons alone. A new research area which uses the inherently force-compliant and back-drivable properties of polymers, ionic polymer–metal composite (IPMC) in this case, has shown potential to undertake precise surgical procedures in the delicate environments related to medical practice. This is because IPMCs have similar actuation characteristics to real biological systems, which can help ensure safety. Despite this, little has been done in developing IPMCs for a rotary joint actuator for functional surgical devices. This research proposes and demonstrates the design of a single degree of freedom (1-DOF) robotic surgical instrument with one skeleton-joint mechanism actuated by IPMC with an embedded strain gauge as a feedback unit. The system performance with a developed gain-schedule PI controller is demonstrated. Despite the simplicity of the system, it was proven to be able to cut to the desired depth using the implemented force control (up to 8 gf cutting force).